Kandungan Bee Bread: Hasil Uji Fitokimia Dan Ftir Pada Bee Bread Sebagai Preliminary Data Suplemen Wanita Prakonsepsi - Annisa Eka Permatasari; Indah Raya; Andi Nilawati Usman; Tuti Sukini; Hamdiah Ahmar (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: This study aims to determine the content of flavonoids and polyphenols found in bee bread. This research is a laboratory research. The sample used in the study was bee bread. Examination used in the form of FTIR test (Fourier Transform Infrared) using FTIR spectrophotometer, Phytochemical Test to see the content of saponins, tannins, flavonoids, alkaloids, terpenoids and steroids using a chemical solution to see the content of bee bread and Polyphenol Test using 20D + Electronics to see the amount of polyphenols on bee bread. This research was conducted at the Integrated Laboratory of the Faculty of Mathematics and Natural Sciences, Hasanuddin University and the Biochemistry Laboratory of the Faculty of Mathematics and Natural Sciences, Hasanuddin UniversityResults: Phytochemical tests using Pb (CH3COO) 2 and FeCl3 reagent solutions were found to contain flavonoids and tannins. While the FTIR test results indicate the existence of a phenolic framework which belongs to the flavonoid group.Conclusion: This study concludes that bee bread contains flavonoids and polyphenols which have antioxidant effects, so it is good to be used in supplements to deal with stress in women.